Respiratory Microbiome Disruption and Risk for Ventilator-Associated Lower Respiratory Tract Infection. (7th August 2021) - Harrigan, James J; Abdallah, Hatem O; Clarke, Erik L; Oganisian, Arman; Roy, Jason A; Lautenbach, Ebbing; Reesey, Emily; Wernovsky, Magda; Tolomeo, Pam; Morawski, Zygmunt; Jacob, Jerry; Grippi, Michael A; et al.
Abstract: Background: Ventilator-associated lower respiratory tract infection (VA-LRTI) is common among critically ill patients and has been associated with increased morbidity and mortality. In acute critical illness, respiratory microbiome disruption indices (MDIs) have been shown to predict risk for VA-LRTI, but their utility beyond the first days of critical illness is unknown. We sought to characterize how MDIs previously shown to predict VA-LRTI at initiation of mechanical ventilation change with prolonged mechanical ventilation, and if they remain associated with VA-LRTI risk. Methods: We developed a cohort of 83 subjects admitted to a long-term acute care hospital due to their prolonged dependence on mechanical ventilation; performed dense, longitudinal sampling of the lower respiratory tract, collecting 1066 specimens; and characterized the lower respiratory microbiome by 16S rRNA sequencing as well as total bacterial abundance by 16S rRNA quantitative polymerase chain reaction. Results: Cross-sectional MDIs, including low Shannon diversity and high total bacterial abundance, were associated with risk for VA-LRTI, but associations had wide posterior credible intervals. Persistent lower respiratory microbiome disruption showed a more robust association with VA-LRTI risk, with each day of (base e) Shannon diversity <2.0 associated with a VA-LRTI odds ratio of 1.36 (95% credible interval, 1.10–1.72). The observed association was consistent across multiple clinical definitions of VA-LRTI. Conclusions: Cross-sectional MDIs have limited ability to discriminate VA-LRTI risk during prolonged mechanical ventilation, but persistent lower respiratory tract microbiome disruption, best characterized by consecutive days with low Shannon diversity, may identify a population at high risk for infection and may help target infection-prevention interventions. Abstract : Persistent lower respiratory tract microbiome disruption, best characterized by consecutive days with low Shannon diversity, identifies a population at high risk for lower respiratory tract infection among patients with prolonged critical illness and dependence on mechanical ventilation.